A simple universal generator for continuous and discrete univariate T-concave distributions. - Leydold, Josef
We use inequalities to design short universal algorithms that can be used to generate random variates from large classes of univariate continuous or discrete distributions (including all log-concave distributions). The expected time is uniformly bounded over all these distributions. The algorithms can be implemented in a few lines of high-level language code. In opposition to other black-box algorithms hardly any setup step is required, and thus it is superior in the changing-parameter case.
Keywords: T-concave distributions; Continuous distributions; Discrete distribution; Log-concave distributions; Nonuniform random variates; Ratio-of-uniforms method; Transformed density rejection; Universal method